Analisis Sistem Akuntansi Persediaan Bahan Penolong Terhadap Pengendalian Internal CV Bumi Nusantara - Sheila Alifanny (UPT Penerbitan Universitas Jember, 2020)
The study aims of analyze and evaluating the accounting system for component inventory and internal control of CV Bumi Nusantara. This type of research is qualitative research with a case study method, through direct observation and structured interviews. Data analysis is performed is an analysis of component inventory systems and analysis of internal controls related to organizational structure in separating duties and responsibilities, authority systems and procedures of enumeration as well as healthy practices that cannot be separated from competent employees. The results showed that the procedures in the accounting system for component inventory carried out by CV Bumi Nusantara has run well but there are still weaknesses and shortcomings in the documents, records and functions related to the system and procedures. There is still a dual role in the function carried out with no separation of duties in the procurement and warehouse division, some documents are not in the company, do not record in the journal. In addition, the physical calculation system that is carried out needs an evaluation because it is only done by the warehouse. A good component inventory accounting system is very influential in improving the internal control of CV Bumi Nusantara because the network of procedures, documents, records and functions will affect the running process of an existing internal control, with the completeness of documents, records, and functions related to the supply of component will facilitate the internal control of CV Bumi Nusantara and improve the level of reliability of accounting information.